Hypnopressure therapy education on postoperative patients at UNS Solo Hospital - Saelan Saelan; Aria Nurahman Hendra Kusuma; Diah Laras Pramesti (Universitas Muhammadiyah Magelang, 2023)
Pain is the main problem that occurs in postoperative patients. Most patients feel discomfort due to surgery, so apart from pharmacological therapy, other therapies are needed to reduce the pain scale. One of them is providing hypnopressure therapy which consists of hypnotherapy and acupressure. The aim of this community service is to provide knowledge of complementary therapy in the form of hypnopressure to postoperative patients at UNS Solo Hospital. Evaluation was carried out using the Numerical Rating Scale (NRS) to measure the pain scale before and after hypnopressure was given. The pain scale measurement results before hypnopressure were given were 5.44 and after therapy were 2.38. These results prove that hypnopressure therapy has succeeded in reducing the postoperative pain scale at UNS Solo Hospital.